2020
DOI: 10.3389/fpls.2020.572264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wounding and Temperature on Resistance of Maize Landraces From Mexico to Aflatoxin Contamination

Abstract: Maize is a staple for billions across the globe. However, in tropical and subtropical regions, maize is frequently contaminated with aflatoxins by Aspergillus section Flavi fungi. There is an ongoing search for sources of aflatoxin resistance in maize to reduce continuous exposures of human populations to those dangerous mycotoxins. Large variability in susceptibility to aflatoxin contamination exists within maize germplasm. In Mexico, several maize landrace (MLR) accessions possess superior resistance to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…TAF and AFB 1 contamination were observed throughout the process points with the highest contamination observed in the raw materials (sesame and soybean). The higher TAF and AFB 1 contamination of sesame and soybean than millet or processed product could be differences in crop structure and or pre and postharvest management according to the respective food types [ [32] , [33] , [34] ]. Similarly, other studies reported differential contamination by aflatoxins due to differences in postharvest practices of many staple crops including oil seeds [ 35 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAF and AFB 1 contamination were observed throughout the process points with the highest contamination observed in the raw materials (sesame and soybean). The higher TAF and AFB 1 contamination of sesame and soybean than millet or processed product could be differences in crop structure and or pre and postharvest management according to the respective food types [ [32] , [33] , [34] ]. Similarly, other studies reported differential contamination by aflatoxins due to differences in postharvest practices of many staple crops including oil seeds [ 35 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…But soybean that was heavily contaminated compared to millet has been shown to have higher tocopherol content compared to millet [ 48 ]. Therefore, susceptibility to fungal infestation and subsequent production of aflatoxins may vary among crop produce depending on their nutrient content, crop structure, and harvest management [ 33 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%